2022
DOI: 10.1088/1758-5090/ac4dd9
|View full text |Cite
|
Sign up to set email alerts
|

Bisulfite-initiated crosslinking of gelatin methacryloyl hydrogels for embedded 3D bioprinting

Abstract: Recent studies on three-dimensional (3D) bioprinting of cell-laden gelatin methacryloyl (GelMA) hydrogels have provided promising outcomes for tissue engineering applications. However, the reliance on the use of photo-induced gelation processes for the bioprinting of GelMA and the lack of an alternative crosslinking process remain major challenges for the fabrication of cell-laden structures. Here, we present a novel crosslinking approach to form cell-laden GelMA hydrogel constructs through 3D embedded bioprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Since the results of the first 3 days are crucial to verify the injury from residual chemicals to cells coming from embedded printing and washing procedure, 34 this study confirmed the great biocompatibility of the HP supporting bath, the embedded printing, and the removal strategy. Although the applied α-CD has a small molecular weight, it is a type of highly safe material for animals and humans and is approved by FDA.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Since the results of the first 3 days are crucial to verify the injury from residual chemicals to cells coming from embedded printing and washing procedure, 34 this study confirmed the great biocompatibility of the HP supporting bath, the embedded printing, and the removal strategy. Although the applied α-CD has a small molecular weight, it is a type of highly safe material for animals and humans and is approved by FDA.…”
Section: Resultssupporting
confidence: 65%
“…While encapsulated in the low-concentration PF-127 (<10%), cells could successfully survive and proliferate. , Though Laponite was added to the PF-127 solution to modify its performance, the addition of CaCl 2 or NaHSO 3 is indispensable, improving the complexity of the material system. Besides, the presence of Laponite makes the bath difficult to be removed. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this nanoclay concentration range, nanoclay platelets present an exfoliated morphology to maintain sufficient yield-stress behavior during printing and the interactions between nanoclay and Pluronic F127 are inhibited with negligible effects. Thus, the dense “house-of-cards” microstructure of nanoclay enables the reported nanocomposites to have a stably high viscosity at any temperatures, making it difficult for adding and/or removing support bath materials by controlling the temperature. Because nanoclay platelets may actively interact with polymer chains in a less-dense intercalated morphology at lower concentrations, in this study, we aim to explore nanoclay-Pluronic F127 with the nanoclay concentration below the threshold value so that an interactive dual microstructure can form for enabling the nanocomposite to present a highly regulable rheology at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, both applied shear stress and temperature change can trigger the reversible phase transition of the nanocomposite. It is noted that the material system consisting of nanoclay and Pluronic F127 has been investigated and used as a matrix bath for 3D bioprinting, 34,35 in which the nanoclay concentration is equivalent to or higher than a threshold concentration (e.g., 3−4% (w/v)). 36 In this nanoclay concentration range, nanoclay platelets present an exfoliated morphology to maintain sufficient yield-stress behavior during printing and the interactions between nanoclay and Pluronic F127 are inhibited with negligible effects.…”
Section: Mechanism Of 3d Printing In Stimuli-responsivementioning
confidence: 99%